A generic micropatterning platform to direct human mesenchymal stem cells from different origins towards myogenic differentiation - Tan, Lay Poh (2013)
Human mesenchymal stem cells (MSCs) derived from various origins show varied differentiation capability. Recent work shows that cell shape manipulation via micropatterning can modulate the differentiation of bone-marrow-derived MSCs. Herein, the effect of micropatterning on the myogenesis of MSCs isolated from three different sources (bone marrow, fetal tissue, and adipose) is reported. All the well-aligned cells, regardless of source, predominantly commit to myogenic lineage, as shown by the significant upregulation of myogenic gene markers and positive myosin heavy chain staining. It is demonstrated that our novel micropattern can be used as a generic platform for inducing myogenesis of MSCs from different sources and may also have the potential to be extended to induce other lineage commitment.